Oxygen Administration Does Not Influence the Prognosis of Acute Myocardial Infarction: A Meta-Analysis. (January 2019) - Khan, Abdur Rahman; Abdulhak, Aref Bin; Luni, Faraz Khan; Farid, Talha A.; Riaz, Haris; Ruzieh, Mohammed; Pham, Long; Hirsch, Glenn; Bolli, Roberto
Abstract : Background: The safety and efficacy of supplemental oxygen in acute myocardial infarction (AMI) remains unclear. Study Question: To evaluate the safety and efficacy of supplemental oxygen in patients who present with AMI. Data Sources: We systematically searched PubMed, Embase, Cochrane Central Register of Controlled Trials, ISI Web of Science, Scopus, and conference proceedings from inception through January 2016. Study Design: Eligible studies were randomized trials that evaluated the role of oxygen compared with room air in AMI. The clinical outcome measured was 30-day mortality, and odds ratio (OR) was calculated for the measured outcome. The Mantel–Haenszel method was used to pool 30-day mortality in a random-effects model. Sensitivity analysis was carried out to evaluate the effect of revascularization of the culprit artery on the outcome. Results: The pooled analysis suggested no difference in 30-day mortality [OR 1.09; 95% confidence interval (CI), 0.30–4.00; P = 0.89] between oxygen and room air. Metaregression demonstrated that all the between-study variance was because of coronary revascularization ( P = 0.01, R 2 = 1.0). A subgroup analysis suggested a trend toward increased mortality with oxygen (OR 3.26; 95% CI, 0.94–11.29; P = 0.06) when less than half of the patient population underwent revascularization. On the other hand, there was a nonsignificant numerical decrease in mortality with oxygen (OR 0.41; 95% CI, 0.14–1.19; P = 0.10) in the presence of coronary revascularization. Metaregression confirmed that all the between-study variance was because of coronary revascularization ( P = 0.01, R 2 = 1.0). Conclusions: In this meta-analysis, we found that the evidence on the safety and efficacy of oxygen was not only weak and inconsistent but also had modest statistical power. The variation in results was mainly because of the presence or absence of revascularization of the culprit artery. Adequately powered studies are needed to further delineate the role of oxygen in patients undergoing coronary revascularization.